How to worry less about money - Armstrong, John, ....- (London : Macmillan, 2012)
Break free of your destructive relationship with money, and learn how money can make you happy,br> Our relationship with money is one that lasts a lifetime. It can be as important as family life, as competitive as work, and as exciting and secretive as love. Yet books about money tend to take one of two routes: a) how to get more, or b) how to deal with less. This book turns these questions upside down, and looks not at money itself, but at the way we view it. How does money drive us? How does it frighten us? And how can it help us make sense of who we are? Money is too important a part of life for us not to worry about, but by approaching it differently, we can change the way we perceive its worth. With surprising and enlightening new insights, How to Worry Less About Money will help you realise what material wealth really means.
Keywords: Geld ; psychologie